Peningkatan Hasil Belajar Siswa Mata Pelajaran Qur’an hadits materi Q.S. An-nasr dan Q.S. Al-kautsar melalui penerapan metode drill kelas IV MIN 8 Aceh Barat Daya - Habibah, Habibah (Universitas Serambi Mekkah, 2020)
This Classroom Action Research discusses the use of the Drill method to improve class IV student learning outcomes in the Hadith Qur'an subjects. His study was motivated by the low ability to memo-rize the Qur'an's Hadith students. This study is intended to answer the problem: (1) Whether the Drill method can improve student learning outcomes in the Al-Quran Hadith subject material Q.S. An-Nasr and Al-Kautsar class IV at MIN 8 Southwest Aceh 2018/2019 Academic Year ?. This type of research used in this study is Classroom Action Research with the nature of CAR carried out independently, which means researchers conduct CAR without collaboration with other teachers, but only involve 1 peer teacher to make observations during the teaching and learning process. Data collection methods used are documentation, observation and test methods. The study was conducted using 2 cycles with the steps of planning, implementing action, observation and reflection. To determine the effectiveness of the Drill method using descriptive analysis techniques. This study shows that learning the subject of the Qur'an in the Hadith Q.S. An-Nasr and Al-Kautsar by using the Drill method can improve student learn-ing outcomes in MIN 8 Southwest Aceh. This can be seen from before the pre cycle, Cycle I and Cycle II an increase in student learning outcomes. the percentage of mastery learning from pre Cycle 41.66%, in Cycle I increased to 62.50% and in Cycle II increased to 83.33%. So there is no need to continue in the next cycle because the KKM and the percentage of completeness have been reached. These findings can be used as material for consideration or input for the school in conducting school quality improve-ment with the improvement of student achievement. For the advice I can convey is that the teacher in carrying out the learning of the Qur'anic Subjects of Hadith is expected to be able to use various learning methods that are tailored to the material being taught, so as to create a pleasant learning atmosphere that can ultimately improve student learning outcomes. Then students should have confidence so that they do not feel afraid to memorize in front of the teacher. In essence, the Drill method can improve student learning outcomes in the subject of the Qur'an Hadith material Q.S. An-Nasr and Al-Kautsar class IV MIN 8 Aceh Barat Daya 2018/2019 Academic Year.